Relative adrenal insufficiency in non-critically ill liver cirrhosis - Agarwal, Dipen; Rao, G. R. Srinivas; Reddy, D. Viswanath; Shankar, B. Ravi (International Journal of Research in Medical Sciences, 2026)
Background: Endocrinopathy like adrenal insufficiency (AI) is being increasingly recognised in patients with liver cirrhosis. It is characterized by a relative decrease in serum cortisol level with respect to increasing stress as occurs in sepsis & has been associated with increased morbidity and mortality. This study aimed to find the prevalence of Adrenal insufficiency and low HDL in non-critically ill chronic liver disease (CLD) patients i.e. patients without sepsis, bleed or dehydration. Methodology: A cross-sectional study including 100 non-critically ill CLD patients aged 20 -80 years. Model for end stage liver disease (MELD) scores and the Child Turcotte Pugh scores (CTP) were used to assess the severity of liver disease. Basal cortisol level was measured & after one hour of short synacthen test (SST), peak and delta cortisol levels were measured in order to assess adrenal function. Biochemical parameters including HDL levels were also assayed. Results: This study included 76 male and 24 female CLD patients. Prevalence of AI was highest in females of age 41-60 years. Alcohol (61%) was the most common etiology, followed by MASLD and HBV. Prevalence of AI was 55.6%, 60.5% and 65.9% in CTP class A, B and C respectively. Prevalence of AI in the high MELD (>15) group was 66.7% and 50% in the low MELD (<14) group. Low HDL and AI were reported in CTP classes B and C. Conclusion: Adrenal insufficiency is common in patients with non-critically ill chronic liver disease; which increases with severity of disease; and whose HDL levels are low.